A Review of the Occurrence of Ovarian Neoplasms in Female Dogs - Sangary, Mohammad (Journal of Natural Sciences – Kabul University, 2025)
Ovarian neoplasms account for 0.5–1.2% of all ovarian tumors detected in bitches. Ovarian tumors in domestic animals are generally classified into three groups: germ cell tumors, sex cord-stromal tumors, and surface epithelial cell tumors. Germ cell tumors typically occur at a young age, while tumors originating from surface epithelial cells of the ovary tend to appear in older dogs (10–12 years old) and account for 40–50% of all ovarian tumors in these animals. The etiology of ovarian tumors in bitches is unknown. Clinical signs associated with ovarian tumors are usually related to the presence of a space-occupying mass within the abdomen or excessive hormone production by the tumor cells. The best treatment for ovarian neoplasms is ovariectomy.